Molecular machines directly observed by high‐speed atomic force microscopy. Issue 8 (11th January 2013) - Ando, Toshio
Abstract : Molecular machines made of proteins are highly dynamic and carry out sophisticated biological functions. The direct and dynamic high‐resolution visualization of molecular machines in action is considered to be the most straightforward approach to understanding how they function but this has long been infeasible until recently. High‐speed atomic force microscopy has recently been realized, making such visualization possible. The captured images of myosin V, F1 ‐ATPase, and bacteriorhodopsin have enabled their dynamic processes and structure dynamics to be revealed in great detail, giving unique and deep insights into their functional mechanisms.